Indicators of Accounting Measurement of Insurance Awareness and its Impact on Risk Reduction in the Light of the International Financial Reporting Standard (Insurance Contracts) - Sainakh, Huda Thamer (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
This study aims to provide some indicators for the accounting measurement to spread insurance awareness and determine its impact on avoiding financial risks in the light of the International Financial Reporting Standard "Insurance Contracts". To achieve this study, the researcher presented the problem of the study and some previous studies related to insurance awareness and accounting for insurance contracts. The researcher presented the main concepts of insurance awareness and its deficiency factors. In addition accounting for insurance contracts, with a focus on testing the adequacy of obligations and displaying the impact on risk reduction. The researcher reached out to provide some indicators to measure insurance awareness. These indicators help to increase the income of insurance companies and avoid the risks arising from insurance contracts. The researcher relied on designing a survey list to test the hypothesis of the study. It was distributed among various groups. The first group consisted of some employees of some insurance companies. The second group consisted of some faculty members in the accounting and insurance departments. The third group consisted of some workers in accounting and auditing offices. The study hypothesis was tested using the SPSS statistical program. The study concluded that the indicators proposed by the researcher to measure the dissemination of insurance awareness can help to avoid the financial risks of the liability adequacy index in insurance companies.